1995
DOI: 10.1097/00003246-199508000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Aspiration-induced lung injury

Abstract: Acid aspiration induces lung injury through a complement-dependent mechanism that leads to microvascular permeability defects. Therefore, the possibility that complement inhibitors may have a salutary effect in humans with aspiration-induced lung injury should be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Commonly used experimental models of ALI include repeated bronchiolar lavage with saline [30], instillation of hydrochloric acid into the tracheobronchial tree [31,32], intravenous infusion of oleic acid [31,33], and intravenous infusion of endotoxin [34]. In a comparative study, Rosenthal et al [35] showed that although each model has its merits, none was closely related to the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly used experimental models of ALI include repeated bronchiolar lavage with saline [30], instillation of hydrochloric acid into the tracheobronchial tree [31,32], intravenous infusion of oleic acid [31,33], and intravenous infusion of endotoxin [34]. In a comparative study, Rosenthal et al [35] showed that although each model has its merits, none was closely related to the clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them were developed in adult-sized animals, and focus on modeling adult respiratory distress syndrome (ARDS), or hypoxia and acute lung injury. Models involving cotton-smoke inhalation,(7, 8) oleic acid instillation,(16) endotoxin injection (9, 17) and hydrochloric acid instillation (18, 19) induce lung injury and strongly activate the systemic inflammatory response, which is not characteristic of pediatric CLD. Saline lavage has been used in pediatric models of acute lung disease since it involves depletion of pulmonary surfactant (20, 21), but does not create PAH and is not generally performed in recovery experiments since severe lung injury is induced (9, 10, 21).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, there is experimental evidence indicating that intravenous IgG may facilitate, through still unknown mechanisms, enhanced migration of polymorphonuclear leukocytes to the site of infl ammation [29] . Complement-mediated sequestration of neutrophils within the pulmonary microvasculature, proposed to play a role in the pathogenesis of meconium aspiration-and acid aspiration-induced acute lung injury [13,30] , is unlikely a contributing factor in our piglets, since high doses of IVIG may prevent complement fragments from binding to target cells [31] . In line with these earlier observations, it may be speculated from our data that, through enhanced local neutrophil migration, IVIG may promote pulmonary removal of aspirated meconium.…”
Section: Discussionmentioning
confidence: 99%